Representação feminina na narrativa infantojuvenil brasileira contemporânea - Leda Cláudia da Silva (Estudos de Literatura Brasileira Contemporânea)
This article investigates female representation turned to the public in question, based on a large research regarding the profile of the personage of the Brazilian contemporary children’s and youth narrative. It is our aim to reflect about the building of the feminine role in a tentative of identifying and questioning matters related to the absence of representation, to the stereotype, or still to the possibility of the literary building of the feminine identity in a multiple and representative manner. The narratives, under examination, were withdrawn from the collection selected and distributed by the Ministry of Education for public schools in Brazil, by means of the National School Library Program. Among the narratives, two shall be studied in detail. Por que meninos têm pés grandes e meninas têm pés pequenos? (Why do boys have big feet and girls have small feet) by Sandra Branco and Amanhecer esmeralda (Emerald Dawn), by Ferréz.